Catalytic Thioglycoside Activation with Diazo-Derived Copper Carbenes - Surya Pratap Singh; Umesh Chaudhary; Indrajeet Sharma (Molecules)
Traditional glycosylation methods using thioglycosides often require harsh conditions or expensive metal catalysts. This study presents a more sustainable alternative by employing copper, an earth-abundant catalyst. We developed diazo-based thioglycoside donors that, through copper catalysis, undergo intramolecular activation to form glycosyl sulfonium ions, leading to the generation of oxocarbenium ions. This versatile approach efficiently accommodates a variety of O-nucleophiles, including primary, secondary, and tertiary, as well as complex bioactive molecules. It is compatible with various glycosyl donors and protecting groups, including superarmed, armed, and disarmed systems. Notably, the methodology operates orthogonally to traditional thioglycoside and alkyne donors and has been successfully applied to the orthogonal iterative synthesis of trisaccharides. Mechanistic insights were gained by studying the electronic effects of electron-donating (OMe) and electron-withdrawing (NO2) groups on the donors, offering a valuable understanding of the intramolecular reaction pathway.